Pengaruh Kualitas Pelayanan Terhadap Kepuasan Masyarakat di Dinas Sosial Provinsi Jawa Timur - Syahbani, Ahmad; Kartika Kusmayati, Nindya; Dhyah Wulansari (Business Administration Dept. - Faculty of Social and Political Sciences, Hang Tuah University, 2024)
The aim of this study is to determine how public satisfaction at the Social Service Office of East Java Province is influenced by service quality. A quantitative strategy involving the investigation of hypotheses related to public satisfaction and service quality is the research technique used. The sample, consisting of 35 respondents, represents the research population, which includes individuals receiving assistance from the Social Service Office of East Java Province. A questionnaire that has been tested for validity and reliability, free from heteroskedasticity, multicollinearity, and normally distributed, is the research tool used. Data were tested using standard linear regression techniques in SPSS 29.0.2.0. The equation Y = 7.669 + 0.765X was obtained using basic linear regression analysis. The research results reveal that high-quality services significantly affect public satisfaction. The determination coefficient of 63.4% indicates that although other factors influence the remaining percentage, service quality impacts public satisfaction. This suggests that the better the service quality, the higher the public satisfaction provided. Therefore, to consistently improve the level of public satisfaction, the Social Service Office of East Java Province must continuously enhance its service quality.